Answer:
[tex]8x^2+8y^2+43-38x+20y=0[/tex]
Step-by-step explanation:
Let [tex]A\left ( x_1,y_1 \right )[/tex] and [tex]B\left ( x_2,y_2 \right )[/tex] be two points then distance AB is equal to [tex]AB=\sqrt{\left ( x_2-x_1 \right )^2+\left ( y_2-y_1 \right )^2}[/tex]
Here, a curve is traced by a point [tex]P(x,y)[/tex] which moves such that its distance from the point [tex]A(-1,1)[/tex] is three times its distance from the point [tex]B(2,-1)[/tex] i.e [tex]AP=3BP[/tex]
Using distance formula,
[tex]AP=\sqrt{(-1-x)^2+(1-y)^2}[/tex]
[tex]BP=\sqrt{(2-x)^2+(-1-y)^2}[/tex]
[tex]AP=3BP\\\sqrt{(-1-x)^2+(1-y)^2}=3\sqrt{(2-x)^2+(-1-y)^2}[/tex]
On squaring both sides, we get
[tex](-1-x)^2+(1-y)^2=9\left [ (2-x)^2+(-1-y)^2 \right ]\\1+x^2+2x+1+y^2-2y=9\left ( 4 +x^2-4x+1+y^2+2y\right )\\1+x^2+2x+1+y^2-2y=36+9x^2-36x+9+9y^2+18y\\8x^2+8y^2+43-38x+20y=0[/tex]
So, equation of curve is [tex]8x^2+8y^2+43-38x+20y=0[/tex]